Effects of a Long-Term Physical Activity Program on Activity Patterns in Older Adults. - Wanigatunga, Amal A; Tudor-Locke, Catrine; Axtell, Robert S; Glynn, Nancy W; King, Abby C; McDermott, Mary M; Fielding, Roger A; Lu, Xiaomin; Pahor, Marco; Manini, Todd M (Medicine and science in sports and exercise, 2017)
PURPOSE: To examine the effect of a long-term structured physical activity (PA) intervention on accelerometer-derived metrics of activity pattern changes in mobility-impaired older adults., METHODS: Participants were randomized to either a PA or health education (HE) program. The PA intervention included a walking regimen with strength, flexibility, and balance training. The HE program featured health-related discussions and a brief upper body stretching routine. Participants (n = 1341) wore a hip-worn accelerometer for >=10 h.d for >=3 d at baseline and again at 6, 12, and 24 months postrandomization. Total PA (TPA)-defined as movements registering 100+ counts per minute-was segmented into the following intensities: low-light PA (LLPA; 100-759 counts per minute), high light PA (HLPA; 760-1040 counts per minute), low moderate PA (LMPA; 1041-2019 counts per minute), and high moderate and greater PA (HMPA; 2020+ counts per minute). Patterns of activity were characterized as bouts (defined as the consecutive minutes within an intensity)., RESULTS: Across groups, TPA decreased an average of 74 min.wk annually. The PA intervention attenuated this effect (PA = -68 vs HE: -112 min.wk, P = 0.002). This attenuation shifted TPA composition by increasing time in LLPA (10+ bouts increased 6 min.wk), HLPA (1+, 2+, 5+, and 10+ bouts increased 6, 3, 2, and 1 min.wk, respectively), LMPA (1+, 2+, 5+, and 10+ bouts increased: 19, 17,16, and 8 min.wk, respectively), and HMPA (1+, 2+, 5+, and 10+ bouts increased 23, 21, 17, and 14 min.wk, respectively)., CONCLUSIONS: The PA intervention increased PA by shifting the composition of activity toward higher-intensity activity in longer-duration bouts. However, a long-term structured PA intervention did not completely eliminate overall declines in total daily activity experienced by mobility-impaired older adults.
Keywords: *Aged/ph [Physiology]; *Exercise; *Health Promotion; ACCELEROMETER; ACTIVITY BOUTS; Accelerometry; Age Factors; Aged; Aged, 80 and over; ELDERLY; Exercise; Female; Health Promotion; Humans; LIGHT-INTENSITY PHYSICAL ACTIVITY; Male; Mobility Limitation; PHYSICAL ACTIVITY INTERVENTION; Program Evaluation; Sedentary Behavior; Sedentary Lifestyle; accelerometry; age; aged; clinical trial; controlled study; dept.hms; exercise; female; health promotion; human; male; multicenter study; peer-reviewed; physiology; program evaluation; randomized controlled trial; sedentary lifestyle; very elderly; walking difficulty

Dose of physical activity, physical functioning and disability risk in mobility-limited older adults: Results from the LIFE study randomized trial. - Fielding, Roger A; Guralnik, Jack M; King, Abby C; Pahor, Marco; McDermott, Mary M; Tudor-Locke, Catrine; Manini, Todd M; Glynn, Nancy W; Marsh, Anthony P; Axtell, Robert S; Hsu, Fang-Chi; Rejeski, W Jack; et al. (PLoS ONE, 2017)
Understanding the minimal dose of physical activity required to achieve improvement in physical functioning and reductions in disability risk is necessary to inform public health recommendations. To examine the effect of physical activity dose on changes in physical functioning and the onset of major mobility disability in The Lifestyle Interventions and Independence for Elders (LIFE) Study. We conducted a multicenter single masked randomized controlled trial that enrolled participants in 2010 and 2011 and followed them for an average of 2.6 years. 1,635 sedentary men and women aged 70-89 years who had functional limitations were randomized to a structured moderate intensity walking, resistance, and flexibility physical activity program or a health education program. Physical activity dose was assessed by 7-day accelerometry and self-report at baseline and 24 months. Outcomes included the 400 m walk gait speed, the Short Physical Performance Battery (SPPB), assessed at baseline, 6, 12, and 24 months, and onset of major mobility disability (objectively defined by loss of ability to walk 400 m in 15 min). When the physical activity arm or the entire sample were stratified by change in physical activity from baseline to 24 months, there was a dose-dependent increase in the change in gait speed and SPPB from baseline at 6, 12, and 24 months. In addition, the magnitude of change in physical activity over 24 months was related to the reduction in the onset of major mobility disability (overall P < 0.001) (highest versus the lowest quartile of physical activity change HR 0.23 ((95% CI:0.10-0.52) P = 0.001) in the physical activity arm. We observed a dose-dependent effect of objectively monitored physical activity on physical functioning and onset of major mobility disability. Relatively small increases (> 48 minutes per week) in regular physical activity participation had significant and clinically meaningful effects on these outcomes., TRIAL REGISTRATION: ClinicalsTrials.gov NCT00116194.
Keywords: *Activities of Daily Living; *Disabled Persons; *Exercise; *Mobility Limitation; Activities of Daily Living; Aged; Aged, 80 and over; Article; Disabled Persons; Exercise; Female; Humans; Male; Mobility Limitation; accelerometry; aged; controlled study; daily life activity; dept.hms; disabled person; education program; exercise; exercise intensity; female; human; incidence; major clinical study; male; multicenter study; outcome assessment; peer-reviewed; physical activity; physical activity, capacity and performance; physical disability; physical functioning; physical mobility; physical performance; randomized controlled trial; resistance training; risk assessment; risk factor; sedentary lifestyle; self report; very elderly; walking difficulty; walking speed

Promoting physical activity for elders with compromised function: the Lifestyle Interventions and Independence for Elders (LIFE) Study physical activity intervention - Rejeski, W. Jack; Axtell, Robert; Fielding, Roger; Katula, Jeffrey; King, Abby C.; Manini, Todd M.; Marsh, Anthony P.; Pahor, Marco; Rego, Alvito; Tudor-Locke, Catrine; Newman, Mark; Walkup, Michael P.; et al. (Clinical Interventions in Aging, 2013)
The Lifestyle Interventions and Independence for Elders (LIFE) Study is a Phase III randomized controlled clinical trial (Clinicaltrials.gov identifier: NCT01072500) that will provide definitive evidence regarding the effect of physical activity (PA) on major mobility disability in older adults (70-89 years old) who have compromised physical function. This paper describes the methods employed in the delivery of the LIFE Study PA intervention, providing insight into how we promoted adherence and monitored the fidelity of treatment. Data are presented on participants' motives and self-perceptions at the onset of the trial along with accelerometry data on patterns of PA during exercise training. Prior to the onset of training, 31.4% of participants noted slight conflict with being able to meet the demands of the program and 6.4% indicated that the degree of conflict would be moderate. Accelerometry data collected during PA training revealed that the average intensity - 1,555 counts/minute for men and 1,237 counts/minute for women - was well below the cutoff point used to classify exercise as being of moderate intensity or higher for adults. Also, a sizable subgroup required one or more rest stops. These data illustrate that it is not feasible to have a single exercise prescription for older adults with compromised function. Moreover, the concept of what constitutes “moderate” exercise or an appropriate volume of work is dictated by the physical capacities of each individual and the level of comfort/stability in actually executing a specific prescription.
Keywords: Accelerometry; Aged; Aged, 80 and over; Aging; Compromised physical function; Exercise; Female; Health Promotion; Humans; Independent Living; Male; Mobility Limitation; Older adults; Physical disability; Qualitative Research; Risk Reduction Behavior; Sex Distribution; accelerometry; aged; aging; article; autoregulation; body mass; compromised physical function; computer interface; computer program; conceptual framework; controlled study; dept.hms; education; elderly care; ethnicity; exercise intensity; female; health education; human; human experiment; lifestyle; male; motor performance; normal human; older adults; phase 3 clinical trial; physical activity; physical capacity; physical disability; quality of life; randomized controlled trial; semi structured interview; sex difference; social behavior; social environment

A case for promoting movement medicine: preventing disability in the LIFE randomized controlled trial - Fanning, Jason; Rejeski, W Jack; Chen, Shyhhuei; Nicklas, Barbara J; Walkup, Michael P; Axtell, Robert S; Fielding, Roger A; Glynn, Nancy W; King, Abby C; Manini, Todd M; Mcdermott, Mary Mcgrae; Newman, Anne B; et al. (Journals of Gerontology Series A-biological Sciences and Medical Sciences, 2019)
Background: The movement profile of older adults with compromised function is unknown, as is the relationship between these profiles and the development of major mobility disability (MMD)-a critical clinical outcome. We first describe the dimensions of movement in older adults with compromised function and then examine whether these dimensions predict the onset of MMD. Methods: Older adults at risk for MMD (N = 1,022, mean age = 78.7 years) were randomized to receive a structured physical activity intervention or health education control. We assessed MMD in 6-month intervals (average follow-up of 2.2 years until incident MMD), with activity assessed at baseline, 6-, 12- and 24-month follow-up via accelerometry. Results: A principal components analysis of 11 accelerometer-derived metrics yielded three components representing lifestyle movement (LM), extended bouts of moderate-to-vigorous physical activity (MVPA), and stationary body posture. LM accounted for the greatest proportion of variance in movement (53%). Within health education, both baseline LM (HR = 0.74; 95% CI 0.62 to 0.88) and moderate-to-vigorous physical activity (HR = 0.69; 95% CI 0.54 to 0.87) were associated with MMD, whereas only LM was associated with MMD within physical activity (HR = 0.74; 95% CI 0.61 to 0.89). There were similar nonlinear relationships present for LM in both physical activity and health education (p ¡ .04), whereby risk for MMD was lower among individuals with higher levels of LM. Conclusions: Both LM and moderate-to-vigorous physical activity should be central in treatment regimens for older adults at risk for MMD.
Keywords: Acceleration; Accelerometry; Age Factors; Aged; Aged, 80 and over; Aging; Confidence Intervals; Disability; Disability Evaluation; Exercise; Female; Geriatric Assessment; Humans; Linear Models; Male; Mobility Limitation; Physical Fitness; Physical activity; Prognosis; Sedentary; Sex Factors; Single-Blind Method; Walking Speed; acceleration; age; aged; aging; clinical trial; confidence interval; controlled study; dept.hms; disability; female; fitness; geriatric assessment; human; male; multicenter study; peer-reviewed; physiology; procedures; prognosis; randomized controlled trial; sex factor; single blind procedure; statistical model; very elderly; walking difficulty; walking speed

Actigraphy features for predicting mobility disability in older adults - Kheirkhahan, Matin; Tudor-Locke, Catrine; Axtell, Robert; Buman, Matthew P.; Fielding, Roger A.; Glynn, Nancy W.; Guralnik, Jack M.; King, Abby C.; White, Daniel K.; Miller, Michael E.; Siddique, Juned; Brubaker, Peter; et al. (Physiological Measurement, 2016)
Actigraphy has attracted much attention for assessing physical activity in the past decade. Many algorithms have been developed to automate the analysis process, but none has targeted a general model to discover related features for detecting or predicting mobility function, or more specifically, mobility impairment and major mobility disability (MMD). Men (N = 357) and women (N = 778) aged 70-89 years wore a tri-axial accelerometer (Actigraph GT3X) on the right hip during free-living conditions for 8.4 +/- 3.0 d. One-second epoch data were summarized into 67 features. Several machine learning techniques were used to select features from the free-living condition to predict mobility impairment, defined as 400 m walking speed ¡0.80 m s(-1). Selected features were also included in a model to predict the first occurrence of MMD-defined as the loss in the ability to walk 400 m. Each method yielded a similar estimate of 400 m walking speed with a root mean square error of similar to 0.07 m s(-1) and an R-squared values ranging from 0.37-0.41. Sensitivity and specificity of identifying slow walkers was approximately 70% and 80% for all methods, respectively. The top five features, which were related to movement pace and amount (activity counts and steps), length in activity engagement (bout length), accumulation patterns of activity, and movement variability significantly improved the prediction of MMD beyond that found with common covariates (age, diseases, anthropometry, etc). This study identified a subset of actigraphy features collected in free-living conditions that are moderately accurate in identifying persons with clinically-assessed mobility impaired and significantly improve the prediction of MMD. These findings suggest that the combination of features as opposed to a specific feature is important to consider when choosing features and/or combinations of features for prediction of mobility phenotypes in older adults.
Keywords: Accelerometers; Actigraphy; Analysis process; Artificial intelligence; Data mining; Disability; Feature extraction; Forecasting; Free livings; General model; Learning systems; Living conditions; Mean square error; Older adults; Patient monitoring; Physical activity; Sedentary; Walking aids; Walking speed; aging; data mining; dept.hms; disability; machine learning; physical activity; sedentary; ⚠️ Invalid DOI

Device-measured physical activity as a predictor of disability in mobility-limited older adults - Mankowski, Robert T.; Anton, Stephen D.; Axtell, Robert; Chen, Shyh-Huei; Fielding, Roger A.; Glynn, Nancy W.; Hsu, Fang-Chi; King, Abby C.; Layne, Andrew S.; Leeuwenburgh, Christiaan; Manini, Todd M.; Marsh, Anthony P.; et al. (Journal of the American Geriatrics Society, 2017)
OBJECTIVES: To examine associations between objectively measured physical activity (PA) and incidence of major mobility disability (MMD) and persistent MMD (PMMD) in older adults in the Lifestyle Interventions and Independence for Elders (LIFE) Study. DESIGN: Prospective cohort of individuals aged 65 and older undergoing structured PA intervention or health education. SETTING: The LIFE Study was a multicenter (eight sites) randomized controlled trial designed to compare the efficacy of a long-term structured PA intervention with that of a health education (HE) program in reducing the incidence of MMD in mobility-limited older adults. PARTICIPANTS: LIFE Study participants (n = 1,590) had a mean age +/- standard deviation of 78.9 +/- 5.2, low levels of PA, and measured mobility-relevant functional impairment at baseline. MEASUREMENTS: Activity data were collected using hip-worn 7-day accelerometers at baseline and 6, 12, and 24 months after randomization to test for associations with incident MMD and PMMD (¿= 2 consecutive instances of MMD). RESULTS: At baseline, every 30 minutes spent being sedentary (¡100 accelerometry counts per minute) was associated with higher rate of subsequent MMD (10%) and PMMD (11%) events. Every 500 steps taken was associated with lower rate of MMD (15%) and PMMD (18%). Similar associations were observed when fitting accelerometry-based PA as a time-dependent variable. CONCLUSION: Accelerometry-based PA levels were strongly associated with MMD and PMMD events in older adults with limited mobility. These results support the importance of daily PA and lower amounts of sedentary time levels in this population and suggest that accelerometry may be a useful tool for assessing risk of mobility disability.
Keywords: Accelerometry; Aged; Aged, 80 and over; Article; Disability Evaluation; Exercise; Female; Geriatric Assessment; Humans; Male; Mini Mental State Examination; Mobility Limitation; Physical Therapy Modalities; Pittsburgh Sleep Quality Index; Sedentary Lifestyle; Time Factors; accelerometry; aged; clinical trial; cohort analysis; controlled study; depression; dept.hms; disability; educational status; ethnic group; exercise; female; functional disease; geriatric assessment; health education; human; major clinical study; major mobility disability; male; marriage; mobility disability; multicenter study; older adults; peer-reviewed; persistent major mobility disability; physical activity; physiotherapy; procedures; prospective study; randomized controlled trial; sedentary lifestyle; sedentary time; sleep quality; time factor; very elderly; walking difficulty